Phase transformation kinetics and microstructure of NiTi shape memory alloy: effect of hydrostatic pressure - Tatar, Cengiz; Yildirim, Zulkuf (Indian Acad Sciences, 2017)
The effect of hydrostatic pressure on the behaviour of reverse and forward transformation temperatures and physical properties of NiTi shape memory alloy has been investigated. The transformation temperatures and physical properties of the alloy change with applied pressure. It has been clearly seen from differential scanning calorimetry that with the increase of applied pressure, while and transformation temperatures decrease, value increases. Moreover, it is obvious that with the increase of applied pressure, Gibbs free energy increases by 5.2883 J, while elastic energy increases by 1.4687 J. In addition, entropy of the alloys decreases by 0.2335 J with applied pressure. Additionally, it is evident from the scanning electron microscopy images of the samples that there is an obvious difference in the grain sizes of the unpressured sample and the samples on which pressure is applied, the sizes being 10-100 and 30-150 , respectively.
Keywords: Phase transformation; differential scanning calorimetry; enthalpy; thermodynamic properties; microstructure